Social Media and Political Mobilization in General Elections in Indonesia - Khamdan, Muh; Fata, Ahmad Khoirul; Macpal, Sunandar; Kamaruzzaman, Kartini (Universitas Islam Negeri Raden Intan Lampung, 2025)
Social media has become a strategic tool in political contests in Indonesia, particularly since the 2014 GeneralElection, the 2017 Jakarta gubernatorial election, and up to the 2024 national elections. This article analyzes the role ofsocial media as a means of political mobilization, framing construction, and discourse dissemination, including its impact on social polarization and political intolerance. This study employs a descriptive-critical qualitative approach, utilizing literature review and digital observation methods to explore the use of platforms such as Twitter (X), Facebook, Instagram, and TikTok during four major political events in Indonesia. The findings indicate that social media is not only effective in shaping political image (e.g., the rebranding of Prabowo Subianto through “gemoy” content), but also serves as a medium for spreading hoaxes, black campaigns, and the exploitation of identity-based issues (religion, ethnicity, and SARA—ethnicity, religion, race, and inter-group relations). Digital buzzers and online volunteers play a pivotal role in influencing public opinion, through both positive and negative campaigning, which has the potential to trigger social conflict. The study further reveals how vertical andhorizontal mobilization strategies including religious, ethnic, and capital-based mobilization contribute to the fragmentation of society. In conclusion, although social media enhances political participation, its adverse effects such as polarization and intolerance must be addressed through stricter regulation of buzzers, civic political education, and risk mitigation by election organizers. These findings offer insight into the dynamics of digital democracy in Indonesia and its implications for social and political stability.